Measurement Of Walking Level In Hypertensive Patients - Dif, Mohamed Bachir; Boumesjed, Abdelkader; Belacel, Hadj (University of Eloued جامعة الوادي, 2023)
This study aimed to know the level of walking activity by comparing it with what is recommended by international organizations, as well as knowing the attitudes of patients with high blood pressure towards walking. The research sample consisted of 356 participants between the ages of 62-78 years with high blood pressure from wilaya ''EL OUED''. Materials: The researchers used the questionnaire to collect data, as the questionnaire was prepared by the researchers, verifying its validity and then distributing it to the participants.Results: The study concluded that 20.79% of the participants walk regularly and 79.21% do not walk regularly.77.25% cover a distance of less than 2 km, 22.75% cover a distance of more than 3 km. 62.64% allocate less than 30 minutes to a session, 37.36% allocate more than 30 minutes to a session. conclusion: level of walking among the participants is less than what is recommended by the international organizations, and him attitudes were negative towards walking.
Keywords: walking; level; hypertension; attitudes